Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.21061/see.52
|View full text |Cite
|
Sign up to set email alerts
|

Early Career Faculty Transitions: Negotiating Legitimacy and Seeking Support in Engineering Education

Abstract: Background: There is limited research exploring the experiences of engineering education scholars transitioning into faculty positions. It is an opportune time to explore these transitions because there is a growing number of scholars identifying with the community, a growing number of doctoral programs being developed, and growing interest in hiring people with engineering education expertise. Purpose/Hypothesis: The purpose of this study is to examine the transitions experienced by our research team of early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Our preliminary work has demonstrated that early-career EES undertake a variety of roles and responsibilities depending on their institutional context. As was identified in McCave et al (2020), there are many types of jobs that EES can pursue, but how EES structure their work within these positions can vary depending on the resources and support they are provided (Coso Strong et al, 2021) and the institutional context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our preliminary work has demonstrated that early-career EES undertake a variety of roles and responsibilities depending on their institutional context. As was identified in McCave et al (2020), there are many types of jobs that EES can pursue, but how EES structure their work within these positions can vary depending on the resources and support they are provided (Coso Strong et al, 2021) and the institutional context.…”
Section: Discussionmentioning
confidence: 99%
“…However, many students lack clarity on the types of roles and responsibilities that exist within engineering education academic positions and how to select the position that would be the best fit for them personally. Similarly, though academic institutions are aware of the value that an engineering education researcher can bring to a department or program (Benson et al, 2010), they lack clarity on how to support Engineering Education Scholars (EES), individuals who have expertise in both engineering education research and practice, and what resources EES need to have their desired impact (Coso Strong et al, 2021).…”
Section: Motivationmentioning
confidence: 99%
“…While our prior work describes our use of collaborative inquiry and collaborative autoethnography (Coso Strong et al, 2021;Faber et al, 2016Faber et al, , 2020, the research design detailed herein emphasizes our use of constructivist grounded theory. We used approaches from constructivist grounded theory because it includes methods to analyze actions and processes, develop conceptual categories from data, and explore the bounds of our theoretical understanding to ultimately construct a contextualized theory (Charmaz, 2014).…”
Section: Sensitizing Conceptsmentioning
confidence: 99%
“…Because our work is situated within our roles and experiences, we provide an overview of our pathways and our desired impact areas at the time we began this project in Table 1. Our prior work focuses on the actions and strategies we used as we transitioned into these positions (Coso Strong et al, 2021). These details provide the context to interpret our results.…”
Section: Continual Reflectionmentioning
confidence: 99%
See 1 more Smart Citation